Low dose Azanucleosides for high risk (s)MDS and AML (Hematology Meeting Reports, 2009)
Azanucleosides like 5-aza- 2’deoxycytidine (Decitabine= Dacogen) and 5-azacytidine (Vidaza) are both cytosine analogues, already synthesised in1964, tested for there cytotoxic capacity when applied in high doses. Using high dose Decitabine therapy for AML patients it became clear that there was a good antileukemic activity but also a high toxicity.